Comparison of treatment response, remission rate and drug adherence in polyarticular juvenile idiopathic arthritis patients treated with etanercept, adalimumab or tocilizumab. Issue 1 (December 2016) - Horneff, Gerd; Klein, Ariane; Klotsche, Jens; Minden, Kirsten; Huppertz, Hans-Iko; Weller-Heinemann, Frank; Kuemmerle-Deschner, Jasmin; Haas, Johannes-Peter; Hospach, Anton
Abstract Background Treatment response, remission rates and compliance in patients with polyarticular juvenile idiopathic arthritis (polyJIA) treated with adalimumab, etanercept, or tocilizumab were analyzed in clinical practice. Methods Data collected in the German BIKER registry were analyzed in patients with polyJIA who started treatment with approved biologics, adalimumab, etanercept or tocilizumab, from 2011 to 2015. Baseline patient characteristics, treatment response, safety and drug survival were compared. Results Two hundred thirty-six patient started adalimumab, 419 etanercept and 74 tocilizumab, with differences in baseline patient characteristics. Baseline Juvenile Disease Activity Score (JADAS)10 (mean ± SD) in the adalimumab/etanercept/tocilizumab cohorts was 12.1+/−7.6, 13.8 ± 7.1 and 15.1 ± 7.4, respectively (adalimumab vs etanercept, p = 0.01), and Childhood Health Assessment Questionnaire (CHAQ)-disability index scores was 0.43 ± 0.58, 0.59 ± 0.6 and 0.63 ± 0.55, respectively (adalimumab vs etanercept, p < 0.001). Uveitis history was more frequent in the adalimumab cohort (OR 5.73;p < 0.001). Balanced patients' samples were obtained by a generalized propensity score to adjust for baseline differences. Pediatric ACR30/50/70/90 criterion improvement after 3 months treatment was achieved by 68%/60%/42%/24% in the etanercept cohort, 67%/59%/43%/27% in the adalimumab cohort and 61%/52%/35%/26% in the tocilizumab cohort. At 24 months, JADAS minimal disease activity was achieved in 52.4%/61.3%/52.4% and JADAS remission in 27.9%/34.8%/27.9% patients in the adalimumab/etanercept/tocilizumab cohorts, respectively. Etanercept was used in 95.5% of patients as a first biologic, adalimumab in 50.8% and tocilizumab in 20.2%. There were no important differences in efficacy between first-line and second-line use of biologics. In total 60.4%/49.4%/31.1% patients discontinued adalimumab/etanercept/tocilizumab, respectively (HR for adalimumab 1.67;p < 0.001; HR for tocilizumab 0.35;p = 0.001). Drug survival rates did not differ significantly in patients on biologic monotherapy compared with combination therapy with methotrexate. Over 4 years observation under etanercept/adalimumab/tocilizumab, 996/386/103 adverse events, and 148/119/26 serious adverse events, respectively, were reported. Conclusions In clinical practice, etanercept is most frequently used as first-line biologic. Adalimumab/etanercept/tocilizumab showed comparable efficacy toward polyJIA. Overall, tolerance was acceptable. Interestingly, compliance was highest with tocilizumab and lowest with adalimumab. This study provides the first indication for the comparison of different biologic agents in polyarticular JIA based on observational study data with all their weaknesses and demonstrates the need for well-controlled head-to-head studies for confirmation.